American public policy : - Peters, B. Guy (Chatham House Publishers, 1996)
This is the new edition of an undergraduate level textbook on the formation and implementation of public policy in the United States. Peters (American government, U. of Pittsburgh) describes the structure of the policy-making system and the process by which policy is enacted.